Therapy and Prevention of Atopic Dermatitis and Psoriasis - Furue, Masutaka; Nakahara, Takeshi; Tsuji, Gaku (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Atopic dermatitis and psoriasis are common inflammatory skin diseases. The excellent therapeutic success of anti-IL-4/IL-13 biologics for atopic dermatitis and anti-TNF-α/IL-23/IL-17A biologics for psoriasis highlights the major pathogenic roles of these cytokines in the respective diseases. Although atopic dermatitis and psoriasis are distinct clinical entities, they share similar inflammatory processes, including increased Th17, Th22, and Th1 signatures. In addition to skin inflammation, both skin diseases exhibit a significant association with systemic diseases such as cardiovascular diseases, metabolic syndrome, and autoimmune diseases. In contrast to atopic dermatitis, males are more susceptible to psoriasis than females. Differential risk factors may be involved in the development and exacerbation in atopic dermatitis and psoriasis. In this issue, we will publish cutting-edge information regarding skin inflammation, clinical aspects, risk factors, microbiome, and therapeutics related to psoriatic and atopic inflammation.